Landesentwicklung durch Freizeitverkehr - Heinze, G. Wolfgang (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
Long-term prognoses point to the unabated growth of leisure and holiday travel. This situation presents an opportunity both to create new jobs and to overhaul our transport system. With the trend towards more frequent, shorter, spontaneous — but all the more intensive — breaks, the distinction between leisure and holiday travel is becoming blurred. Foreign travel — in pursuit of either the sun or snow — continues to be popular, but globalisation entails not only the opening up of new markets, but also the rediscovery of local identity, with the focus on intimacy, niches and group. An appropriate strategy to pursue in central Europe would therefore be “More Frequent Short-Break Travel in Place of Long-Stay Tourism”. Germany is on its way to becoming a boring country. And yet the popularity of active sports and events suggests that there is a strong desire to experience something which contrast with everyday life. Instead of promoting standardisation and copying others, spatial planning and transport policy should be more daring in the field of leisure travel. It should encourage distinctiveness, creative provincialisation and partnerships among contrasting locations.
Keywords: Article